Ascites in children with extrahepatic portal venous obstruction: Etiology, risk factors and outcome. Issue 12 (December 2020) - Sen Sarma, Moinak; Srivastava, Anshu; Yachha, Surender Kumar; Poddar, Ujjal
Abstract: Background: Ascites in extrahepatic portal venous obstruction (EHPVO)  is uncommon. We studied the etiology and natural history of ascites and risk factors of post-bleeding ascites in children with EHPVO. Methods: All admitted EHPVO patients with clinically detectable ascites and/or gastrointestinal (GI) bleeding in previous 6 weeks were analysed. Subjects with ascites were classified as post-bleeding ascites and de-novo ascites (no GI bleeding) Post-bleeding ascites group was compared with controls (GI bleeding without ascites) for risk factors of developing ascites. Results: Of the total 307 analysed EHPVO patients, 26% ( n =79) had ascites. Majority ( n =66, 83%) were post-bleeding ascites and 17% ( n =13) had de-novo ascites due to secondary causes. Risk factors of ascites in post-bleeding ascites ( n =56) versus controls ( n =188) were younger age of disease onset, lower height z-scores and greater reduction in serum protein, albumin and hemoglobin from baseline non-bled state. 32%, 39%, and 29% of patients with post-bleeding ascites had ascites resolution with salt restriction, additional diuretics and large volume paracentesis respectively. Conclusions: Majority of ascites in EHPVO children is after GI bleeding where early age of disease onset, large volume of blood loss and poor nutritional status are risk factors. Overall outcome of EHPVO with ascites is favourable.